(untitled) (Historia, 2021)
1. RICHARD ELPHICK and HERMAN GILIOMEE (eds.) The shaping of South African society, 1652-1840 (2nd edition) 2. BERNARD LUGAN Histoire de l frique du Sud de l’Antiquitea nosjours 3. M. SIENAERT-VAN REENEN Die Franse bydrae tot Africana-literatuur 1622-1902 4. B.J.T. LEVERTON (ed.) Record of Natal, Volume Two, September 1828 - July 1835 5. ROGER C. FISHER en SCHALK LE ROUX (samestell Die Afrikaanse Woning: hedrukke uit ’Die Boerevrou’ 6. GEORGE HOLMES (red.) The Oxford Rlustrated history of Medieval Europe